Baccharis rectialata (Compositae: Astereae): a new species of carqueja from Uruguay - Valtierra, María Victoria; Marchesi, Eduardo; Heiden, Gustavo; Bonifacino, José M. (Phytotaxa, 2021)
Baccharis rectialata (Compositae: Astereae), a new species of B. sect. Caulopterae from the grasslands in northeastern Uruguay is described. The new species is morphologically similar to B. crispa and can be differentiated by its straight wing margins, shorter involucres and pappus in staminate capitula. We provide a detailed morphological description, and information on the distribution, habitat, phenology, and conservation status. Additionally, we discuss the main differences between B. rectialata and other closely related and morphologically similar species, and provide a key for identification of subshrubs belonging to B. sect. Caulopterae occurring in Uruguay, as well as illustrations, images, and a distribution map of the new species.